Need Analysis of Tax Education for Non-Accounting Program: Evidence from Nigerian Universities - Mustapha, Bojuwon; Olaleye, Banji Rildwan; Olanike, Oshatimi Omowumi; Olowookere, Johnson Kolawole (International Business Education Journal, 2021)
This paper examines the need analysis of tax education for non-accounting program by identifying an area of preference in taxation, tax knowledge, tax policy, tax rules and regulation, tax culture and the instructional method of teaching. Questionnaires were administered to 1,200 undergraduates of non-accounting programmes in Nigerian private and public universities. Data were analyses using SPSS to obtain descriptive statistics and one sample t-test results. Based on the survey, the respondents indicated that the introduction of tax education to non-accounting programmes in Nigerian universities is important and relevant to the development of the nation. It also revealed that tax policy, tax rules and regulation together with tax culture for individuals are the preferred tax areas that undergraduates want to understand. This paper is in line with the government initiative to increase awareness on tax rules and regulation, tax culture and knowledge to improve the level of compliance among the taxpayers.